The Social Media Manifesto - Hallam, Jed. (Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2013)
The Social Media Manifesto is a handbook to enable leaders across the business to understand how social technology can be incorporated into their company. Including case studies from Google, IBM, Spotify, Unilever, and Coca-Cola, it provides insight and practical advice for managers to implement their own social business plans.